1980
DOI: 10.1073/pnas.77.4.2323
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activation induced by infusion of endorphins into the ventral tegmental area: evidence for opiate-dopamine interactions.

Abstract: ,-Endorphin in nanomole quantities produced a stimulation of locomotor activity when infused into the region of the dopamine cell bodies of the ventral tegmental area (VTA) in rats. a-, -y-, and des-Tyr-y-endorphin produced similar effects, but the D-alanine analogues of a-and y-endorphin produced a larger and longer-lasting activation, presumably reflecting their resistance to degradation. This locomotor activation was reversible by pretreatment with naloxone and b destruction of the terminal projections of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(51 citation statements)
references
References 24 publications
(28 reference statements)
2
49
0
Order By: Relevance
“…A marked difference with systemic administration is that upon intra-VTA administration, the locomotor effects of opioids seem to be completely dopamine-dependent (Kelley et al 1980;Stinus et al 1980;Joyce et al 1981;Kalivas et al 1983), mediated by indirect stimulation of mesolimbic dopaminergic neurons (Johnson and North 1992;Klitenick et al 1992). Given the findings that the mesolimbic dopaminergic system becomes hyperreactive upon repeated treatment with psychostimulant drugs (see introduction), it is therefore not surprising that in these studies cross-sensitization to intra-VTA morphine was observed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A marked difference with systemic administration is that upon intra-VTA administration, the locomotor effects of opioids seem to be completely dopamine-dependent (Kelley et al 1980;Stinus et al 1980;Joyce et al 1981;Kalivas et al 1983), mediated by indirect stimulation of mesolimbic dopaminergic neurons (Johnson and North 1992;Klitenick et al 1992). Given the findings that the mesolimbic dopaminergic system becomes hyperreactive upon repeated treatment with psychostimulant drugs (see introduction), it is therefore not surprising that in these studies cross-sensitization to intra-VTA morphine was observed.…”
Section: Discussionmentioning
confidence: 95%
“…The locomotor activating properties of psychostimulant drugs are generally thought to be due to an increase in nucleus accumbens dopaminergic neurotransmission (Kelly et al 1975;Pijnenburg et al 1975;Delfs et al 1990; for review see Amalric and Koob 1993). On the other hand, the psychomotor effects of opioid drugs have been shown to involve both dopamine-dependent and dopamine-independent components (Pert and Sivit 1979;Kelley et al 1980;Stinus et al 1980;Joyce et al 1981;Kalivas et al 1983;Vaccarino et al 1986). This leaves open as to whether expression of opioid sensitization involves hyperresponsiveness of dopaminergic and/or non-dopaminergic mechanisms, and whether sensitization to opioids and psychostimulant requires different neuroadaptive phenomena.…”
mentioning
confidence: 99%
“…Furthermore, the specific opioid ligand involved in MOR activation in VTA has not been identified. Anatomical studies show both beta-endorphin (Mansour et al, 1988) and enkephalin (Johnson et al, 1980;Fallon and Leslie, 1986) terminals in the VTA, and pharmacological evidence shows that both of these peptides can activate the mesolimbic DA system (Broekkamp et al, 1979;Stinus et al, 1980;Dauge et al, 1992). In addition, recent reports have indicated the presence of the highly MOR-specific ligands endomorphin-1 and -2 in the VTA (Greenwell et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As pioneered by the Segal laboratory and others, animal models of locomotor behavior have been critical tools for understanding the relationships between monoamines and behavior (Geyer and Segal, 1991;Kelly and Iversen, 1976;Lat, 1965;Schiorring, 1979;Segal et al, 1975Segal et al, , 1971Segal and Mandell, 1970;Stinus et al, 1980). Such behavioral models have provided a foundation for much of what we know regarding the neural correlates of behavioral effects of drugs of abuse, in particular psychotomimetics such as stimulants and hallucinogens (Adams and Geyer, 1982;Bankson and Cunningham, 2001;Creese, 1983;Eilam et al, 1989;Fink and Morgenstern, 1985;Geyer, 1990;Lehmann-Masten and Geyer, 1991;Segal, 1975;Segal et al, 1981Segal et al, , 1980Swerdlow and Koob, 1985).…”
Section: Introductionmentioning
confidence: 99%